PENERAPAN PERATURAN TATA TERTIB SEKOLAH DALAM MENAGGULANGI SISWA YANG MELANGGAR ATURAN DI SMA NEGERI 8 PONTIANAK - Yuni Widyaningsih; Supriadi Supriadi; Izhar Salim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract: The purpose of this research is to Entitled Application of School Rules and Regulations in Dealing with Students Who Break Rules in SMA Negeri 8 Pontianak. The problem in this study is "How is the application in school order, constraints and results in Tackling Students Who Violate Rules At SMA Negeri 8 Pontianak?". The method used is descriptive with a qualitative approach. The results showed that: 1). Implementation of school rules that include direction, counseling, distribution of pocket books to students. 2). The obstacle that is found in the application of school rules is that there are still many students who break the rules, such as being late, leaving at the change of class time. 3). The result of its application is to carry out mild sanctions, verbal warnings in the form of guidance given by BK teachers to students who break the rules. The medium sanction is in the form of a valid Statement 3 times. Severe sanctions in the form of suspension, returns to parents of students. Keywords: Implementation, Order, School.